Nucleus Accumbens-Associated Protein 1 Expression Has Potential as a Marker for Distinguishing Oral Epithelial Dysplasia and Squamous Cell Carcinoma - Sekine, Joji (PLoS One, 2015)
BACKGROUND: Oral epithelial dysplasia (OED) and carcinoma in situ (CIS) are defined by dysplastic cells in the epithelium. Over a third of oral squamous cell carcinoma (OSCC) patients present with associated OED. However, accurate histopathological diagnosis of such lesions is difficult. Nucleus accumbens-associated protein 1 (NAC1) is a member of the Pox virus and Zinc finger/Bric-a-brac Tramtrack Broad complex family of proteins, and is overexpressed in OSCC. This study aimed to determine whether NAC1 has the potential to be used as a marker to distinguish OED and OSCC. METHODS AND FINDINGS: The study included 114 patients (64 men, 50 women). There were 67, 10, and 37 patients with OED, CIS, and OSCC, respectively. NAC1 labeling indices (LIs) and immunoreactivity intensities (IRI) were evaluated. The patients’ pathological classification was significantly associated with age, sex, NAC1 LIs, and NAC1 IRI (p = 0.025, p = 0.022, p < 0.001, and p < 0.001, respectively). As a result of multivariate analysis, a predictive model was made; this identified the NAC1 LIs (OR [95% CI] 1.18 [1.11–1.28], p < 0.001) and NAC1 IRI (0.78 [0.68–0.86], p < 0.001) as predictive factors for CIS/OSCC. The NAC1 LIs/IRI cut-off values which discriminated between OED and CIS/OSCC were 50%/124 pixels. For NAC1 LIs with > 50% positivity the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 0.766, 0.910, 0.857, and 0.847, respectively. For NAC1 IRI with ≤ 124 positive pixels, the sensitivity, specificity, PPV, and NPV were 0.787, 0.866, 0.804, and 0.853, respectively. Though there are several potential limitations to this study and the results were obtained from a retrospective analysis of a single site cohort, the data suggest that the NAC1 LIs/IRI is a strong predictor of CIS/OSCC. CONCLUSIONS: NAC1 has potential as a marker for distinguishing OED from CIS/OSCC.